Initial assessment and monitoring of nutritional status and malignant pain in lung cancer patients - Karabatić, Sandra (Array, 2020)
Introduction. Lung cancer is a complex disease and requires a multidisciplinary approach to achieve the best results in treatment, to increase the survival rate while preserving the quality of life of the sufferer. The nutritional status of the patient is an important factor affecting outcome and recovery from disease or injury. We question whether there is a link between nutritional status and malignant pain in lung cancer patients. Aim. A prospective trial was conducted to determine the distribution of respondents by frequency of pain according to a validated Visual Analog Scale (VAS), distribution of respondents who reported reduced food intake and distribution of factors that have led to the reduced food intake. Methods. A prospective trial was conducted at the Department for respiratory diseases Jordanovac, University Hospital Center Zagreb, Croatia, on a sample of patients with advanced non-small cell lung cancer to determine the frequency, characteristics and treatment of chronic malignant pain (N=76). These are the results from November 2013 to June 2014. For pain assessment, we used a validated VAS. For the identification of patients at risk of malnutrition we used Nutritional risk screening tool (NRS 2002). For a rough estimate of total body adiposity, we measured dermal thicknesses using a standard calliper. Monitoring of patients was documented in the form of nursing documentation. A component of nursing documentation was designed to monitor the nutritional status of cancer patients and has been implemented at the Department for respiratory diseases Jordanovac as required documentation. The component included collecting the following data: the stage and type of cancer and treatment, demographic characteristics, age, gender, vital signs, body weight and height, body mass index (BMI), subjective symptoms such as pain, fatigue and nausea, reduction ad rezones of food consumption. Results.